Changes in Retinal N‐Acylethanolamines and their Oxylipin Derivatives During the Development of Visual Impairment in a Mouse Model for Glaucoma. Issue 7 (24th May 2016) - Montgomery, Christa L.; Keereetaweep, Jantana; Johnson, Heather M.; Grillo, Stephanie L.; Chapman, Kent D.; Koulen, Peter
Abstract: Neurons are especially susceptible to oxidative damage, which is increasingly implicated in neurodegenerative disease. Certain N ‐acylethanolamines (NAEs) have been shown to protect neurons from oxidative stress. Since glaucoma may be considered a neurodegenerative disorder and the survival of retinal neurons could also be influenced by N ‐acylethanolamines, our goal was to quantify changes in certain N ‐acylethanolamine species and their oxylipin derivatives in the retina of a mouse model for glaucoma. We also sought to identify relationships between these and parameters of glaucoma disease development, specifically intraocular pressure, visual acuity, and contrast sensitivity. Five N ‐acylethanolamine species and three NAE oxylipin derivatives were quantified in retina from young and aged DBA/2Crl mice. N ‐Acylethanolamines and NAE‐oxylipins in retinal extracts were quantified against deuterated standards by isotope dilution gas chromatography–mass spectrometry. Levels (nmol/g dry weight) of N ‐arachidonoylethanolamine (anandamide; NAE 20:4) were significantly ( p = 0.008) decreased in aged (2.875 ± 0.6702) compared to young animals (5.175 ± 0.971). Conversely, the anandamide oxylipin, 15(S)‐HETE ethanolamide (15(S)‐HETE EA), was significantly ( p = 0.042) increased in aged (0.063 ± 0.009) compared to young animals (0.039 ± 0.011). Enzymatic depletion of the anandamide pool by 15‐lipoxygenase and consequent accumulation of 15(S)‐HETE ethanolamine may contribute to decreased visual function in glaucomatous mice. Since N ‐acylethanolamines effectively attenuate glaucoma pathogenesis and associated visual impairment, our data provides additional rationale and novel targets for glaucoma therapies.